2021
DOI: 10.1039/d1ta02293h
|View full text |Cite
|
Sign up to set email alerts
|

Rate dependent structural changes, cycling stability, and Li-ion diffusivity in a layered–layered oxide cathode material after prolonged cycling

Abstract: Li-rich layered oxide (LLO) cathode materials, xLi2MnO3·(1-x)LiCoO2 (0<x<1, M= Mn, Ni, Co, etc.) are considered promising cathode materials in Li-ion batteries for large scale applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Similar to the cycling stability test result, the sample with 20 minutes of microwave treatment shows the optimum rate capability, which can be related to the high c/a ratio of this sample. A high c/a ratio enlarges the layer spacing, facilitating a facile Li ion diffusion and providing a large capacity at the high current density [46].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the cycling stability test result, the sample with 20 minutes of microwave treatment shows the optimum rate capability, which can be related to the high c/a ratio of this sample. A high c/a ratio enlarges the layer spacing, facilitating a facile Li ion diffusion and providing a large capacity at the high current density [46].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the activation of Li 2 MnO 3 to form an LiMnO 2 phase can induce a spinel-like phase transition during cycling. Previous reports revealed that the degree of Li 2 MnO 3 activation was largely determined by the Li 2 MnO 3 domain size and current rate 33,42,43 . A small Li 2 MnO 3 domain size and low current rate could facilitate activation of the Li 2 MnO 3 phase and subsequently cause a large initial irreversible capacity and a spinel-like phase transition, leading to poor cyclability.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…It was found that the more time spent at high potentials, the more structural defects that were formed. Yin et al [148] also studied the structural evolution of the material during a constant voltage of 5 h after being fully charged to 4.8 V and found a new phase produced under continuous oxidation at this stage, which aggravated the migration of Mn and the deterioration of capacity and voltage.…”
Section: Regulating Activationmentioning
confidence: 99%